Pengaruh Strategi Learning Start With A Question Terhadap Hasil Belajar di MI Tarbiyatul Banat - Nur Hafizatul Munadliroh; Kiky Chandra Silvia Anggraini (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2022)
One of the factors that affect a student's learning outcomes is the learning strategy used by the teacher. Implementation of the Learning Start With A Question strategy This study aims to determine the effect of student learning outcomes. Strategy and students who are taught using conventional learning strategies in class III. The method used in this study is a quantitative research method with the type of research Pre-experimental Design in the form of One-group Pretest-posttest. Based on the results of the Pretest which initially got an average value of 60.00, it increased in the posttest by getting an average value of 78.40. The results of the calculation of the t-test Ha is accepted that there is a significant influence on the implementation of the Learning Start With A Question learning strategy on the learning outcomes of the Thematic subjects Theme 8 Sub-theme 2 class III students of MI Tarbiyatul Banat